In vivo Guinea Pig Model Study for Evaluating Antifungal Effect of a Dual-Diode Laser with Wavelengths of 405 Nm and 635 Nm on Dermatophytosis - Ahn JC; Mo SJ; Choi M; Kim B; Cho SB (Dove Medical Press, 2023)
Jin-Chul Ahn,1,* Sang Joon Mo,1,* Min Choi,2 Bora Kim,2 Sung Bin Cho3 1Medical Laser Research Center, College of Medicine, Dankook University, Cheonan, Korea; 2R&D Center, Shenb Co., Ltd, Seoul, Korea; 3Yonsei Seran Dermatology and Laser Clinic, Seoul, Korea*These authors contributed equally to this workCorrespondence: Sung Bin Cho, Yonsei Seran Dermatology and Laser Clinic, Geumcheon REMAIN CITY 6F, 224 Siheung-Daero, Geumcheon-Gu, Seoul, 08628, Korea, Tel +82 2-2135-1375, Fax +82 70-8250-1375, Email drsbcho@gmail.comBackground: Various laser- and light-based devices have been introduced as complementary or alternative treatment modalities for dermatophytosis, particularly for finger or toenail onychomycosis.Objective: This study aimed to comparatively evaluate the antifungal effects of 405-nm and 635-nm dual-band diode lasers using an in vivo guinea pig model of dermatophytosis.Materials and Methods: A guinea pig model was developed by the repetitive application of fungal spore preparations to the back skin of guinea pigs. Dual-diode laser treatment was delivered to the guinea pig skin at a power of 24 mW at a wavelength of 405 nm and 18 mW at 635 nm for 12 min. The treatments were administered three times weekly for 2 weeks, and a mycological study was performed.Results: Mycological studies using scraped samples obtained from treatment groups A (N = 8) and B (N = 8) after dual-diode laser treatment revealed that seven of eight (87.5%) samples in each group had negative results for direct potassium hydroxide microscopy and fungal culture studies. Skin specimens from each infected laser-untreated guinea pig exhibited spongiotic psoriasiform epidermis with parakeratosis. Meanwhile, skin specimens from infected laser-treated guinea pigs in groups A and B demonstrated thinner epidermal thickness than those from infected untreated controls but thicker than those from uninfected treated controls without noticeable inflammatory cell infiltration in the dermis.Conclusion: The guinea pig dermatophytosis model can be used to comparatively evaluate the efficacy and safety of various treatment modalities, including dual-diode lasers, for superficial fungal skin infection.Keywords: dermatophytosis, Trichophyton rubrum, Trichophyton mentagrophytes, skin, toenail, dual-diode laser, wavelengths of 405 nm and 635 nm